Analisis Nilai Budaya dalam Cerita Rakyat Etnik Serawai Bengkulu - Rhima Intan Kurniasih; Fina Hiasa; Emi Agustina (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study aims to collect Serawai ethnic folktales, analyze their narrative structures, and identify the cultural values embedded within them. The research employs a qualitative descriptive method using structural and cultural value approaches. Data were obtained through interviews with informants, resulting in the collection of six Serawai folktales, namely Si Pahit Lidah (Serunting Sakti), Dusun Tinggi (Sebakas), Danau Kuranding, Batu Balai, Misteri Bukit Candi, and Sepit Kancing. The analysis focuses on structural elements, including theme, plot, characters and characterization, and setting, followed by an examination of cultural values using Clyde Kluckhohn’s cultural value orientation theory. The findings show that the six folktales are constructed through the integration of narrative elements that form a unified meaning and convey moral and cultural messages to the community. The dominant character, Serunting Sakti, represents wisdom, moral responsibility, and leadership. Furthermore, the analysis reveals that Serawai folktales contain five cultural value orientations proposed by Kluckhohn: the nature of human life, human work, human relations with time, human relations with nature, and human relations with others. These values are reflected in attitudes of wisdom, honesty, responsibility, hard work, appreciation of experience, environmental awareness, mutual cooperation, deliberation, and respect for customary traditions. Among these orientations, the most dominant is human relations with others. Overall, Serawai folktales function as oral literary heritage and as a medium for transmitting cultural values, preserving local wisdom, and strengthening Serawai cultural identity.